Recent Seismicity in the Area of the Major, 1908 Messina Straits Earthquake, South Italy - Neri, Giancarlo; Orecchio, Barbara; Presti, Debora; Scolaro, Silvia; Totaro, Cristina (Frontiers in Earth Science, 2021)
High-quality non-linear hypocenter locations and waveform inversion focal mechanisms of recent, shallow earthquakes of the Messina Straits have allowed us to obtain the following main results: (i) seismicity has occurred below the east-dipping north-striking fault proposed by most investigators as the source of the 1908, magnitude 7.1 Messina earthquake, while it has been substantially absent in correspondence of the fault and above it; (ii) earthquake locations and related strain space distributions do not exhibit well defined trends reflecting specific faults but they mark the existence of seismogenic rock volumes below the 1908 fault representing primary weakness zones of a quite fractured medium; (iii) focal mechanisms reveal normal and right-lateral faulting in the Straits, reverse faulting at the southern border of it (Ionian sea south of the Ionian fault), and normal faulting at the northern border (southeastern Tyrrhenian sea offshore southern Calabria); (iv) these faulting regimes are compatible with the transitional character of the Messina Straits between the zone of rollback of the in-depth continuous Ionian subducting slab (southern Calabria) and the collisional zone where the subduction slab did already undergo detachment (southwest of the Ionian fault); (v) the whole seismicity of the study area, including also the less recent earthquakes analyzed by previous workers, is compared to patterns of geodetic horizontal strain and uplift rates available from the literature. We believe that the joint action of Africa-Europe plate convergence and rollback of the Ionian subducting slab plays a primary role as regard to the local dynamics and seismicity of the Messina Straits area. At the same time, low horizontal strain rates and large spatial variations of uplift rate observed in this area of strong normal-faulting earthquakes lead us to include a new preliminary hypothesis of deep-seated sources concurring to local vertical dynamics into the current debate on the geodynamics of the study region.